Evaluation of Lateral Incisor Resorption Caused by Impacted Maxillary Canines Based on CBCT: A Systematic Review and Meta-Analysis - Anastasia Mitsea; Georgia Palikaraki; Konstantinos Karamesinis; Heleni Vastardis; Sotiria Gizani; Iosif Sifakakis (MDPI AG, 2022)
Background: Root resorption (RR) of the adjacent teeth due to upper canine impaction requires an appropriate modification of the orthodontic treatment plan and the mechanotherapy used. Aim: The aim of this review was to assess scientific evidence published during the last decade, concerning the prevalence of lateral incisor RR caused by impacted maxillary canines, based only on cone-beam computed tomography (CBCT). The location of RR on this tooth, as well as the prevalence of RR on the other adjacent teeth, were additionally evaluated. Methods: This review followed the criteria specified by the PRISMA statement. Four databases were searched for articles published between January 2008 and June 2021. Predefined and piloted data collection forms were used to record the necessary information. Results: A total of 5098 records were initially screened. Only seven articles were finally eligible for further analysis. A total number of 540 participants (176 males and 364 females) was derived from the included studies. RR of maxillary lateral incisors was common (50%). RR of mild severity was more common (62%), more frequently located in the middle (52%) and apical (42%) thirds of the root. Conclusions: Further research with more homogeneous groups is required.